Validation of group decisions: why and when perceived group heterogeneity is relevant - Lopes, D. (2014)
Based on the attributional reformulation of social comparison theory (Goethals &Darley, 1977) and on previous studies (e.g., Lopes, Vala, &Garcia-Marques, 2007), the present research extends our understanding of the role of group consensus and heterogeneity on attribution of validity to group opinions and decisions. One experimental study tested the hypothesis that the effect of group heterogeneity on the validity attributed to group decisions is mediated by the perceived group participation when group consensus is high, but not when group consensus is low. The results support this mediated moderation hypothesis and are discussed in the light of the epis-temic value of heterogeneity and consensus information in group decisions and opinions.